Mapeamento e modelagem de processos pela abordagem Business Process Modeling Notation: uma experiência de trabalho na Pró-Reitoria de Assistência e Promoção ao Estudante da Universidade Federal da Paraíba - Costa, Marivete Santos da (2020)
The Federal University of Paraíba (UFPB), with more than 30,000 active students, has a large percentage of students who need student assistance. The operationalization of the student assistance policy – the Pro-Rectory of Student Assistance and Promotion (PRAPE), however, has represented a constant challenge for managers. The present research had as general objective to model key organizational processes implemented by PRAPE, aiming to contribute to improve the operationalization of the management of the student assistance policy aimed at undergraduate students at UFPB. In recent decades, Business Process Management – BPM (Business Process Management), an approach to organizational management through processes, which offers strategic benefits that allow organizations to react to periods of rapid change, has been consolidated in companies private institutions and, although incipient, has been adopted by some federal higher education institutions (IFES). In the BPM implementation processes, the Business Process Modeling Notation (BPMN) tool has been adopted for the identification, analysis and modeling of processes, essential for an integrated and efficient coordination of activities. BPMN is a set of graphical standards that facilitate visualization and simplify understanding of organizational processes. In order to address these issues and achieve the general objective proposed, the following specific objectives were defined: 1) Mapping key organizational processes of Student Assistance, implemented by PRAPE/UFPB. 2) Analyze the mapped processes, based on ISO/TR 26122:2008 and AVA; and 3) Presenting proposals for process improvements. The proposal had the character of applied qualitative research, exploratory and descriptive. For the implementation of the work, the action research (AP) method was adopted, considering that this is a method that emphasizes collective participation, co-learning and organizational transformation. Among the results achieved, two key processes were mapped and modeled – granting student aid (with two sub-processes linked to it) and payment of student aid; as well as a greater knowledge base was built, on the part of the servants who participated in the research, about what the main organizational processes of Student Assistance managed by PRAPE/UFPB are and how they work.